Primary and metastatic mucinous adenocarcinomas of the ovary: Evaluation of the diagnostic approach using tumor size and laterality - Surapan Khunamornpong (2018)
Objective. To evaluate the usefulness of the recently proposed algorithm (Seidman JD, Kurman RJ, Ronnett BM. Primary and metastatic mucinous adenocarcinomas in the ovaries: incidence in routine practice with a new approach to improve intraoperative diagnosis. Am J Surg Pathol 2003; 27: 985-93 [5]) that classifies mucinous adenocarcinomas of the ovary as primary when they were unilateral ≥10 cm and as metastatic when they were unilateral <10 cm or bilateral. Methods. Malignant ovarian neoplasms, which were resected in Chiang Mai University Hospital between 1992 and 2003, were histologically reviewed. Mucinous adenocarcinomas involving the ovary were identified. The medical records and radiologic materials were reviewed in correlation with the pathologic features to identify the primary site. Results. There were 74 cases of mucinous adenocarcinomas; 16 were primary ovarian; 52, metastatic; and 6 of indeterminate primary site (primary versus metastatic). Primary mucinous adenocarcinomas had a mean size of 16.4 cm and bilateral involvement in 13%. Metastatic mucinous adenocarcinomas had a mean size of 11.7 cm and bilateral involvement in 77%. Excluding the 6 tumors of indeterminate primary site, the proposed algorithm correctly classified primary and metastatic tumors in 84% of 68 cases. Of 21 unilateral mucinous adenocarcinomas ≥10 cm, 62% were primary ovarian. Of 5 unilateral tumors <10 cm, 80% were metastatic. Of 42 bilateral mucinous adenocarcinomas, 95% were metastatic. Conclusion. The algorithm provided high accuracy in the overall prediction of primary and metastatic mucinous adenocarcinomas of the ovary, with major strength in the identification of metastatic tumors by bilaterality or size < 10 cm. However, the prediction of primary mucinous adenocarcinomas by unilaterality and size ≥10 cm was less reliable than previously reported. Due to the overlapping features between primary and metastatic tumors and the higher frequency of the latter, the possibility of metastases should always be borne in mind in the evaluation of mucinous adenocarcinomas of the ovary. © 2005 Elsevier Inc. All rights reserved.